2017
DOI: 10.1093/pcp/pcx006
|View full text |Cite
|
Sign up to set email alerts
|

Basic Pentacysteine Proteins Repress Abscisic Acid Insensitive4 Expression via Direct Recruitment of the Polycomb-Repressive Complex 2 in Arabidopsis Root Development

Abstract: Plant transcription factors generally act in complex regulatory networks that function at multiple levels to govern plant developmental programs. Dissection of the interconnections among different classes of transcription factors can elucidate these regulatory networks and thus improve our understanding of plant development. Here, we investigated the molecular and functional relationships of the transcription factors ABSCISIC ACID INSENSITIVE 4 (ABI4) and members of the BASIC PENTACYSTEINE (BPC) family in late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 78 publications
5
65
0
Order By: Relevance
“…BPC6 has been shown to participate in the regulation of ABI4 (Mu et al, 2017), and subcellular localization indicated that BPC6-GFP is in the nucleus of guard cells (Figure 7A). To detect whether BPCs can directly regulate the expression of key marker genes of stomatal development, we analyzed the transcript levels of both SCRM and SCRM2 , which can form a complex to regulate the functions of SPCH, MUTE, and FAMA (Pillitteri and Torii, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BPC6 has been shown to participate in the regulation of ABI4 (Mu et al, 2017), and subcellular localization indicated that BPC6-GFP is in the nucleus of guard cells (Figure 7A). To detect whether BPCs can directly regulate the expression of key marker genes of stomatal development, we analyzed the transcript levels of both SCRM and SCRM2 , which can form a complex to regulate the functions of SPCH, MUTE, and FAMA (Pillitteri and Torii, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Expression of BPC genes occurs widely, but to different extents, in various organs. These genes play important roles in regulating the vegetative and reproductive development (Kooiker et al, 2005; Monfared et al, 2011; Simonini et al, 2012; Simonini and Kater, 2014; Mu et al, 2017; Shanks et al, 2018). Our results indicate that besides the core TFs (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In this model (Figure 8), the BPCs, type-B ARRs and CRFs co-regulate gene expression by either independently binding to different cis-acting elements to convergently regulate target gene expression or by binding to elements as part of the same transcriptional complex. The BPCs may also recruit other complexes to these genes such as the PRC chromatin modifiers to promote or repress transcription of target genes (Hecker et al, 2015;Mu et al, 2017;Xiao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The BPCs interact with Polycomb-Repressive Complex 1 (PRC1) proteins, which form protein complexes that remodel chromatin by modifying histone tails to repress transcription of genes (Mu et al, 2017;Xiao et al, 2017). Furthermore, BPC6, a class II BPC, interacts with a member of the PRC1 complex, LIKE HETEROCHROMATIN 1 (LHP1) and recruits LHP1 to GAGA binding motifs and the PRC2 member Vernalization 2 (VRN2) was shown to associate with BPC6 via LHP1 in vivo (Hecker et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation